1999
DOI: 10.1029/1999jb900186
|View full text |Cite
|
Sign up to set email alerts
|

A relative geomagnetic paleointensity stack from Ontong‐Java Plateau sediments for the Matuyama

Abstract: We present a stack of geomagnetic paleointensity estimates for the Matuyama Chron (0.778–2.582 Ma). Sedimentary magnetizations from 4 Ocean Drilling Program (ODP) cores from the Ontong‐Java Plateau (OJP) are analyzed with thermal techniques. Thellier‐Thellier experiments are used to determine magnetic properties and indicate that a thermal treatment to 250°C can be used for paleointensity estimates. The correlated records form a coherent OJP stack, which is dated at reversal boundaries. A coherent feature with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 24 publications
5
60
0
Order By: Relevance
“…Useful insight on the origin of tiny wiggles can however be gained from the few available highresolution magnetostratigraphic paleointensity studies covering the past few Myr (see for instance, [25] for the Brunhes period; [26] for the Matuyama period; [27] for the Matuyama and late Gauss periods; [9] for the past 2 Myr; [8] for the past 4 Myr; [28] for chrons 5n; [29] for chrons 6Bn to 13n; [30] for chrons 12r to 13r). These studies have shown that the magnetic polarity time scale mainly determined from marine magnetic anomalies is almost complete and that only a few tiny wiggles detected so far can be ascribed to additional short polarity intervals (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Useful insight on the origin of tiny wiggles can however be gained from the few available highresolution magnetostratigraphic paleointensity studies covering the past few Myr (see for instance, [25] for the Brunhes period; [26] for the Matuyama period; [27] for the Matuyama and late Gauss periods; [9] for the past 2 Myr; [8] for the past 4 Myr; [28] for chrons 5n; [29] for chrons 6Bn to 13n; [30] for chrons 12r to 13r). These studies have shown that the magnetic polarity time scale mainly determined from marine magnetic anomalies is almost complete and that only a few tiny wiggles detected so far can be ascribed to additional short polarity intervals (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, from the Santa Rosa I dome ( Fig. 1 40 Ar/ 36 Ar intercept was 281.8 þ 9.4, signi¢cantly lower than the atmospheric value of 295.5, which is di⁄cult to explain for terrestrial volcanic rocks [18]. From a split of the same sanidine separate analyzed by Doell et al [17] from the Santa Rosa I rhyolite, Izett and Obradovich [3] obtained total fusion measurements from six multigrain aliquots that de¢ne a weighted mean age of 930 þ 17 ka.…”
Section: Geologic Setting and Previous Workmentioning
confidence: 99%
“…Following three additional minutes of clean up on a single SAES C-50 getter, the gas from each heating step was expanded into a Mass Analyser Products-215-50 spectrometer ¢tted with a Nier type ion source, the mass range 40^36 was scanned eight times in static mode using a Balzers SEV-17 electron multiplier, and its initial composition determined by regression analysis. System blanks were measured before every fourth sample and for 40 Ar were one to two orders of magnitude smaller than the samples (V10 317 mol), whereas for 36 Ar blanks typically comprised 10^90% of the signal (V10 319 mol), but were stable during analytical periods of several hours per session.…”
Section: Paleomagnetic Andmentioning
confidence: 99%
“…A rapid progress in paleointensity estimation using marine sediment cores in 1990s resulted in the establishment of the global paleointensity stack during the Brunhes chron: the Sint-800 of Guyodo and Valet (1999). Efforts have been made to extend the paleointensity record to older periods, and an increasing number of records in the Matuyama chron have been published (Valet and Meynadier, 1993;Meynadier et al, 1994;Sato et al, 1998;Kok and Tauxe, 1999;Channell et al, 2002;Yamazaki andOda, 2002, 2005;Carcaillet et al, 2003;Horng et al, 2003). However, agreement among the records is not very good (Yamazaki and Oda, 2005).…”
Section: Introductionmentioning
confidence: 99%